Genghis Khan - Salvador, Lou.; Conde, Manuel ([S.l. s.n.], 1953)
This colorful if somewhat truncated biopic of the legendary mongol leader was filmed in the Philippines. Manuel Conde (the film's producer) stars as Temujin, the peasant later to be known as Genghis Khan. In rapid-fire order, Temujin fights a rival tribe over the rights to water hole, avenges the murder of his father, and claims the heroine (Elvira Reyes).
DVD
Manuel Conde, Elvira Reyes, Lou Salvador.
Keywords: Historical films; Feature films